Implementation Personality Development Programs as a Mechanism of Social Control in Correctional Institutions - Rahmayanti, Echa; Imran, Imran; Wahyuni, Fauziah Sri; Zakso, Amrazi; Zatalini, Adhalia (Jurnal Pendidikan Sosiologi dan Humaniora, 2025)
This study aims to analyze the implementation of the personality development program as a social control mechanism in the Sungai Raya Class II Special Child Development Institution, which includes three main aspects, namely, planning, implementation, and program implementation results. This study uses a qualitative approach with a descriptive type. Data collection techniques through observation, interviews, and documentation. Informants are determined by purposive sampling technique based on certain criteria that have been set. The results of this study show that the implementation of the personality development program as a social control mechanism at the Sungai Raya Class II Special Children's Development Institution has been effective in strengthening internal social control, so that the behavior of the fostered children becomes better and positive, both mentally and socially. Program implementation planning has been carried out systematically through program determination, success indicators, those in charge of implementing the program and compiling a structured schedule of activities. The implementation of the personality development program consists of a religious development program implemented by the Ministry of Religion of Pontianak City and an intellectual development program implemented by the Community Learning Activity Center (PKBM) Khadijah Kubu Raya. The results of the program implementation show that there are positive changes in attitudes, behaviors, active involvement both psychologically and emotionally, discipline in participating in activities, and increasing religious and intellectual knowledge of the fostered children. Thus, this research is expected to be an academic reference and provide practical benefits in the development and implementation of programs.